2022
DOI: 10.21037/qims-21-322
|View full text |Cite
|
Sign up to set email alerts
|

Hyperattenuations on flat-panel computed tomography after successful recanalization of mechanical thrombectomy for anterior circulation occlusion

Abstract: Background: To evaluate intraparenchymal hyperattenuation (IPH) on flat-panel computed tomography (FPCT) findings and their clinical usefulness for predicting prognosis after successful mechanical thrombectomy (MT) for acute occlusion of anterior circulation.Methods: A retrospective review was conducted for 158 consecutive patients undergoing mechanical thrombectomy during the last six years. After excluding those with posterior circulation occlusion or incomplete recanalization and those without FPCT, 82 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Several studies have reported that hyperdense areas are independently associated with both purely radiological and symptomatic post-EVT ICH. 61,62,67 Larger hyperdense areas are associated with higher risks of ICH. Further studies using dual-energy CT may help to decipher what these hyperdensities represent.…”
Section: Hyperdensities On Flat-panel Ct or Early Noncontrast Ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that hyperdense areas are independently associated with both purely radiological and symptomatic post-EVT ICH. 61,62,67 Larger hyperdense areas are associated with higher risks of ICH. Further studies using dual-energy CT may help to decipher what these hyperdensities represent.…”
Section: Hyperdensities On Flat-panel Ct or Early Noncontrast Ctmentioning
confidence: 99%
“…Following EVT, a focal hyperdense area is commonly observed on CT either acquired in the angiosuite using flat-panel CT or using standard CT immediately following EVT (Figure 2). 61,62,67 Such hyperdense areas may be a sign of iodine contrast leakage, bleeding, or a combination of both and more generally reflect BBB damage. Several studies have reported that hyperdense areas are independently associated with both purely radiological and symptomatic post-EVT ICH.…”
Section: Early Posttreatment Imaging Biomarkers Of Post-evt Ichmentioning
confidence: 99%
“…The efficacy of endovascular treatments for acute ischemic stroke has been substantiated by several recent randomized clinical trials, and endovascular intervention received the strongest level I recommendation in recent American Heart Association/American Stroke Association guidelines ( 1 , 2 ). However, complex vascular anatomy and chronic lesions involving extracranial or intracranial vessels may make classical anterograde approaches through parent vessels challenging.…”
Section: Introductionmentioning
confidence: 99%
“…It helped save time, enhance the efficiency, and improve the clinical prognosis of the patient. However, cross-circulation approaches are also associated with potential risks, such as long procedure times (puncture to recanalization), hemorrhagic complications, and thromboembolic events in unaffected arterial territories ( 2 - 5 ). We report a clinical case of acute ischemic stroke in two simultaneous circulation systems due to the occlusion of intracranial arteries that was resolved by a cross-circulation mechanical thrombectomy procedure.…”
Section: Introductionmentioning
confidence: 99%